Comparison Review of Two Regulatory Agencies Regulation: Therapeutic Goods Administration (TGA) and the European Medicine Agency (EMA) in Relation to Good Manufacturing Practice (GMP) Guideline - Farida Aziza (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
There are some regulatory bodies in the world that impacting the pharmaceutical industry to operate and perform Good Manufacturing Practice (GMP) principles. These regulatory bodies exist to ensure that the pharmaceutical product and other human supporting products have a high standard of quality, safety, and efficacy from product registration to product distribution to the patient. This article reviews some aspects which is regulated by two of regulatory entities including Therapeutic Goods Administration (TGA) and European Medicines Agency (EMA) in relation with Good Manufacturing Practice (GMP) principles. The GMP principles which is structured by these regulatory agencies may be originally created by the agencies or influenced by other regulatory body concepts. The guidance can be a primary source or second reference for the pharmaceutical industry in impacting countries depending on the guideline’s legal status. It is noticeable that both regulatory bodies have some similar concepts to support GMP implementation and some differentt practices which may be considered by the pharmaceutical industry when it is aimed to market their product in the regulated countries.